Analysis of the knowledge of Nurses working in an inpatient unit on cardiorespiratory arrest (Research, Society and Development, 2025)
This study aims to analyze the knowledge of nurses working in an inpatient unit about Cardiopulmonary Arrest (CPA). This is a quantitative, exploratory, and cross-sectional study conducted at a University Hospital in northern Ceará. Data collection was carried out from October 2023 to January 2024. Two questionnaires were used: a professional training profile questionnaire and a questionnaire on CPA, validated by a previous study by Alves et al. (2019). Data collection was done online (Google Forms). Excel (2013), Windows®, was used for data organization, tabulating the data and performing simple statistical analysis. The Likert metric was used to assess satisfaction with the results obtained. The results of the professional training profile reveal that 76.7% are female; 94% have completed more than two years since graduation; 85% are between 24 and 40 years old; 80% have worked in the sector studied for more than one year; 72.4% have worked in other healthcare facilities; and 56.7% reported having taken extracurricular or postgraduate courses in emergency medicine that addressed the topic studied. Knowledge of cardiac arrest (CPR) was unsatisfactory, with more than 50% (n=5+11) scoring between poor and fair. This highlights the importance of encouraging professional development and continuing education for professionals and institutions.